Acute Total Uterine Inversion: A Life Threatening Obstetrics Emergency - Shrestha, Reena; Shrestha, SD; Malla, AP; Pradhan, R; Pradhan, B; RC, Laxmi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Acute total uterine inversion is a rare and life threatening obstetric emergency. Prompt diagnosis and aggressive management reduces maternal mortality and morbidity .We report a case of 28 year old primi, who had total uterine inversion immediately after normal delivery of full term baby weighing 3150gm. Immediate manual repositioning was done by Johnson’s maneuver under general anesthesia. She recovered well and was discharged after 5 days.